ANALISIS URAIAN TUGAS TENAGA ADMINISTRASI SEKOLAH BIDANG KEPEGAWAIAN SLTA DI PULAU SIPORA KABUPATEN KEPULAUAN MENTAWAI - Yosi Angel Dirawati; Rusdinal Rusdinal; Nelitawati Nelitawati; Yulianto Santoso (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of job descriptions for School Administrative Staff in personnel management at senior secondary schools on Sipora Island, Mentawai Islands, evaluate task alignment, identify implementation gap triggers, and examine adaptive strategies. A descriptive qualitative approach was employed, involving eight informants across four schools. Data were gathered via in-depth interviews, observations, and document reviews. Data validity was tested through triangulation, and analysis followed Miles and Huberman’s interactive model. Results show that alignment between formal job descriptions and daily practice reached 70–80%. The gap is driven by five factors: human resource competency, geographical-infrastructural constraints, institutional dynamics, absence of written SOPs, and workload imbalances. Schools and staff responded through task reallocation and self-directed learning. This study provides empirical insights into implementation gaps in remote archipelagic (3T) regions, demonstrating how geographical isolation exacerbates structural weaknesses in formal job descriptions.